Konstruksi Kausatif Analitik Bahasa Nias dengan Pendekatan Teori X-Bar - Wartono Wartono; Mulyadi Mulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article analyzes the analytic causative construction in the Nias language using the X-Bar Theory and vP-Shell framework of generative syntax. The study aims to describe its internal structural pattern and determine its clausal status. Data were collected through interviews with native speakers of the Gunungsitoli dialect and analyzed qualitatively using a series of syntactic tests. The results reveal three main findings. First, the analytic causative construction in Nias follows a consistent basic pattern: V.CAUS + Causee + V + Causer, realized by the lexical causative verbs mube’e, böröta, and fatenge. Second, hierarchical analysis reveals a double-layered structure where the causative verb functions as the head taking the resultant event clause as its complement. Third, through passivization and binding tests, the construction is proven to realize two clausal statuses: integrated monoclausal and biclausal with clear clausal boundaries. This variation reflects the grammatical flexibility of Nias and provides empirical evidence for the clause integration continuum theory. This study contributes to the linguistic documentation of Nias and enriches typological discussions on causative realization in non-SVO Austronesian languages.